Orthodontic Movement of Central Incisor with Previously-healed Root Fracture associated with Unerupted Canines - Maio Pinzan-Vercelino, CÃ©lia Regina; Pozzobon Pereira, Alex Luiz; Salvatore Freitas, Karina Maria; Matos Nogueira, MarÃlia; Alves Campos, CÃ¡ssio Bernard; AraÃºjo Gurgel, JÃºlio; Monteiro Bramante, ClÃ³vis (Iranian Endodontic Journal, 2021)
Teeth with root fracture may need orthodontic treatment. This case report presents the management of unerupted canines in a patient with previously-healed/untreated horizontal root fracture in the maxillary left central incisor. The malocclusion was treated maintaining pulp vitality considering the principles to improve the eruption path of maxillary canines and move short-rooted teeth. The root-fractured tooth remained symptomless after orthodontic treatment without significant adverse effects, and stayed stable following 2-year follow-up.